Hydrogen Does Not Appear To Be a Major Electron Donor for Symbiosis with the Deep-Sea Hydrothermal Vent Tubeworm Riftia pachyptila - Mitchell, Jessica H. (Appl Environ Microbiol, 2019)
Use of hydrogen gas (H(2)) as an electron donor is common among free-living chemolithotrophic microorganisms. Given the presence of this dissolved gas at deep-sea hydrothermal vents, it has been suggested that it may also be a major electron donor for the free-living and symbiotic chemolithoautotrophic bacteria that are the primary producers at these sites. Giant Riftia pachyptila siboglinid tubeworms and their symbiotic bacteria (“Candidatus Endoriftia persephone”) dominate many vents in the Eastern Pacific, and their use of sulfide as a major electron donor has been documented. Genes encoding hydrogenase are present in the “Ca. Endoriftia persephone” genome, and proteome data suggest that these genes are expressed. In this study, high-pressure respirometry of intact R. pachyptila and incubations of trophosome homogenate were used to determine whether this symbiotic association could also use H(2) as a major electron donor. Measured rates of H(2) uptake by intact R. pachyptila in high-pressure respirometers were similar to rates measured in the absence of tubeworms. Oxygen uptake rates in the presence of H(2) were always markedly lower than those measured in the presence of sulfide, as was the incorporation of (13)C-labeled dissolved inorganic carbon. Carbon fixation by trophosome homogenate was not stimulated by H(2), nor was hydrogenase activity detectable in these samples. Though genes encoding [NiFe] group 1e and [NiFe] group 3b hydrogenases are present in the genome and transcribed, it does not appear that H(2) is a major electron donor for this system, and it may instead play a role in intracellular redox homeostasis. IMPORTANCE Despite the presence of hydrogenase genes, transcripts, and proteins in the “Ca. Endoriftia persephone” genome, transcriptome, and proteome, it does not appear that R. pachyptila can use H(2) as a major electron donor. For many uncultivable microorganisms, omic analyses are the basis for inferences about their activities in situ. However, as is apparent from the study reported here, there are dangers in extrapolating from omics data to function, and it is essential, whenever possible, to verify functions predicted from omics data with physiological and biochemical measurements.